(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article focuses on the role of games in a literary texts of famous contemporary writer T. Tolstaya, that is relevant in modern Russian literature and culture in general. The study of the poetic texts T. Tolstaya directs the study of the role of contrast imagined and depicted, ways to organize links in the text between author and reader, game allusions, visible and hidden quotations, that characterize contemporary culture. On the example of T.Tolstaya’s texts with pronounced intertextual features are studied especially the using of «alien word» for the emergence of a dialogue of the author and the reader. Revealed features T. Tolstaya worldview influenced by the experience of Vladimir Nabokov, his experimental style. The results of observations show that the clash of «voices» in the plot and style allow modern writers to express new meanings by relating them to previously known. This way enable to better understand the ways of influencing the text on the reader, to clarify the relationship of the author and the reader as communicants with equal rights, and determine the depth of the relationship in contemporary culture.